CLINICAL OBSERVATION OF SEVERE ITSENKO-CUSHING DISEASE - Daminov , A.T; Norkulov , Alijon; Turamudov , Rahim; Zayniddinova , Dinora (Educational Research in Universal Sciences, 2024)
Itsenko-Cushing disease is a serious disease of the neuroendocrine system caused by excessive release of adrenocorticotropic hormone by a pituitary tumor. The incidence of this disease is 39.1 cases per 1 million population, and the incidence is from 1.2 to 2.4 cases per 1 million. Typical symptoms include rapid weight gain combined with muscle weakness, hypertension, diabetes mellitus and osteoporosis . The main diagnostic method is MRI of the brain after laboratory confirmation of hypercortisolemia, and the main treatment method is transnasaladenomectomy, which allows achieving remission in 65–90% of cases. This article describes a clinical observation of severe Itsenko-Cushing disease, which remained undiagnosed for a long time. The stages of the diagnostic search, the difficulties of differential diagnosis and the results of dynamic observation, including selective blood sampling from the inferior petrosal sinuses are considered. A multidisciplinary approach and teamwork make it possible to ensure timely diagnosis, prevent the development of complications of Itsenko-Cushing disease, and improve the patient’s prognosis and quality of life.